Activation of the aryl hydrocarbon receptor affects activation and function of human monocyte-derived dendritic cells. (9th July 2014) - Wang, C; Ye, Z; Kijlstra, A; Zhou, Y; Yang, P
Summary: Aryl hydrocarbon receptor (AhR) is well known for mediating the toxic effects of dioxin-containing pollutants, but has also been shown to be involved in the natural regulation of the immune response. In this study, we investigated the effect of AhR activation by its endogenous ligands 6-formylindolo[3, 2-b]carbazole (FICZ) and 2-(1′H-indole-3′-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE) on the differentiation, maturation and function of monocyte-derived DCs in Behçet's disease (BD) patients. In this study, we showed that AhR activation by FICZ and ITE down-regulated the expression of co-stimulatory molecules including human leucocyte antigen D-related (HLA-DR), CD80 and CD86, while it had no effect on the expression of CD83 and CD40 on DCs derived from BD patients and normal controls. Lipopolysaccharide (LPS)-treated dendritic cells (DCs) from active BD patients showed a higher level of interleukin (IL)-1β, IL-6, IL-23 and tumour necrosis factor (TNF)-α production. FICZ or ITE significantly inhibited the production of IL-1β, IL-6, IL-23 and TNF-α, but induced IL-10 production by DCs derived from active BD patients and normal controls. FICZ or ITE-treated DCs significantly inhibited the T helper type 17 (Th17) and Th1 cell response. Activation of AhR either by FICZ or ITE inhibits DC differentiation, maturation and function. Further studies are needed to investigate whether manipulation of the AhR pathway may be used to treat BD or other autoimmune diseases.